Gastrointestinal and Psychiatric Symptoms Among Children and Adolescents With Autism Spectrum Disorder - Neuhaus, Emily; Bernier, Raphael A.; Tham, See Wan; Webb, Sara J. (Frontiers in Psychiatry, 2018)
Individuals with autism spectrum disorder (ASD) are at heightened risk of psychiatric comorbidities across the lifespan, including elevated rates of internalizing, externalizing, and self-injurious behaviors. Identification of medical comorbidities that contribute to these concerns may elucidate mechanisms through which psychiatric concerns arise, as well as offer additional avenues for intervention. Gastrointestinal (GI) conditions are of particular interest, as they are prevalent among those with ASD, may share genetic or neurobiological etiologies with the core features of ASD, and are linked with psychiatric difficulties in the general population. In this paper, we draw on data from nearly 2800 children and adolescents with ASD within the Simons Simplex Collection to characterize the unique contributions of (1) autism symptoms, (2) psychosocial factors (child’s age, sex, verbal and nonverbal IQ, adaptive behavior, race, and household income), and (3) GI concerns with respect to multiple psychiatric outcomes. Multiple regression models revealed unique contributions of ASD symptoms and multiple psychosocial factors such as verbal IQ, adaptive behavior, and family income to internalizing, externalizing, and self-injurious behavior. In general, higher levels of psychiatric symptoms were associated with more ASD symptoms, higher verbal IQ, lower adaptive behavior skills, and lower family income. Furthermore, levels of GI symptoms accounted for unique variance in psychiatric outcomes over and above these other factors, linking increased GI problems with increased psychiatric symptoms in children with ASD. Taken together, results indicate that the presence and quantity of GI symptoms should be considered when evaluating psychiatric and behavioral concerns among children with ASD, and that treatment of GI conditions may be an important component in alleviating a broad array of mental health concerns in this group.